**answer 2**

It is convenient to work with pairs of points on the graph from right to left. Between 1 and 2, the graph goes through 4 and goes down by 1, so the slope is -1/4 Between 0 and 1, the graph goes through 4 and goes down by 2, so the slope is -2/4 = – 1/2 can see a trend here. For each leftmost unit interval, the slope doubles. We therefore have … 1 ≤ x ≤ 2: -0.25 0 ≤ x ≤ 1: -0.5 -1 ≤ x ≤ 0: -1 -2 ≤ x ≤ -1: -2 The average slope over the longest intervals will be the average slopes in the intervals (of the same length) that make up the longest interval. -2 ≤ x ≤ 0: average of -2 and -1, so -1.5 0 ≤ x ≤ 2: average of -0.5 and -0.25, so -0.375 Going through the numbers in your list here, the matching (range, slope) pairs are… (1, 3), (2, 5), (3, 2), (4, 4), (5, 6), (6, 1)

**answer 3**

Walkthrough: 1. cannot answer because there is no positive number 2. -1.5, -1, -2 3. -2, -1.5, -1 4. again cannot answer because there is there is no positive number 5. -1, -5, -0.375, -0.25 6. again there is no answer because there is no positive number

**answer 4**

Given q(x) = (x + 3)^2 1.) The average rate of change of q(x) in the interval -6 ≤ x ≤ -4 is given by 2.) The average rate of change of q( x ) in the interval -3 ≤ x ≤ 0 is given by 3.) The average rate of change of q(x) in the interval -6 ≤ x ≤ -3 is given by 4.) The average rate rate of change of q(x) in the interval -3 ≤ x ≤ -2 is given by 5.) The average rate of change of q(x) in the interval -4 ≤ x ≤ -3 is given by 6. ) The average rate of change of q(x) in the interval -6 ≤ x ≤ 0 is given by

**Answer 1**

3,1,4,2,5,6 Step by step explanation:

Related Posts

HELP ASAP A circle is shown. Secant A D and tangent E D intersect at point D outside of the circle. Secant A D intersects the circle
Answer 2C) 10(a + 10) = 12 2 Step by step explanation: on the edgeAnswer 3Tangent²=(Any secant segment)(External secant segment) 2. Any secant segment is: AD=a+12 3. O exterior the segment secant is: BD=10 4. The tangent segment is: DE=12 5. So you have: DE²=ADxBD 12²=(a+10)10 10(a+10)=12² 6. So the answer is the third option : 10(a+10)=12²Answer 6c.) 10(a+10)=12^2 Step by step explanation: answer on the edge 2020, I just did the test, I hope it helped!!! Answer 8c'est sur le bord Walkthrough: d on edgeAnswer 4th answer is the last option: x(2x+4)=(x+2)2 WalkthroughAnswer 7is D on edge Walkthrough:Answer 10 The secant theorem e of the tangent states: If a tangent segment and a secant segment are drawn on a circle from an outer point, then the square of the measure of the tangent segment is equal to the product of the measures of the secant segment and its outer secant segment. In the given figure DE is tangent and AD is the secant By applying the theorem we have: BD.AB=DE^{2} Substituting the values of the figure 10(a+10)=12^{2} Answer 5x( 2x+ 4) = (x+2)^2Answer 1C) 10(a+10) = 12 2Answer 6c.) 10(a+10)=12^2 Walkthrough: answer within 2020, just passed the test hope Read more

On a coordinate plane, 2 triangles are shown. Triangle A B C has points (negative 4, 4), (negative 4, 1), and (0, 1). Triangle W R
In a coordinate plane, 2 triangles are represented. Triangle ABC has points (4.4 minus), (4.1 minus) and (0.1). Triangle WRS has points (0, minus 1), (1.75, 1.5), (5, minus 1). In the diagram, △ABC ≅ △WRS. What is the scope of △WRS? 10 pieces 11 pieces 12 pieces 13 piecesAnswer 1Walkthrough (C)12 units: Triangle WRS has points W(0, -1), R(1.75, 1.5), and S(5, -1). WRS triangle perimeteranswer 212 units I just passed the good luck test (:answer 3The third option is correct. Step by step explanation: As we have shown that △ABC ≅ △WRS So the perimeter of △ABC is given by AB+BC+CA here, AB = 3 units BC = 4 units AC = x By the Pythagorean theorem, we get that Then the perimeter of △ABC is 3+4+5=12 units So the perimeter of △WRS is also 12 units because they are similar triangles. So the third option is correct.answer 4The answer is 12 Walkthrough:Answer 6The correct answer is 12 units (in edgenuity)Answer 7The correct answer in e2020 is C. 12 unitsAnswer 8c Step by step explanation: go all the way

What is Mathway? – Mathway and Cheating
What is Mathway? Do you also use educational platforms to study? Then this article will guide you about such a Mathway educational app besides this article.Forging technologies and their involvement in our daily lives have become inseparable. Every morning when a person wakes up there is something new in the world of technology, be it in any field like education, sports, networking and more. Technology has helped mankind solve countless problems, but everything has a downside as well. If not used sparingly, technology can also have a detrimental impact on humanity. Technology and issues may seem unrelated or seem clichéd, but they are two sides of the same coin. As much as we involve ourselves in technology, we also have great privileges and obstacles.One of those debatable topics “Technology, boon or curse for students” was covered later in this article. With the impact of the Covid-19 pandemic, education has been geared towards technology, with online education being the only option for students. That said, it has both positive and negative effects on students. If used wisely with jurisdictions, technology is one of the greatest things that has ever happened; but without any control it can be harmful beyond expectation. One Read more

What is the additive inverse of the polynomial?
What is the additive inverse of the polynomial? –6×3 + 4×2 – 4xAnswer 1Walkthrough: Additive inverse is also known as negation, -1 times the original. We negate every term.answer 26x³ – 4x² + 4x Walkthrough: The additive inverse is the value added to make the expression equal to zero. Given – 6x³ + 4x² – 4x, then the additive inverse is – ( – 6x³ + 4x² – 4x) = 6x³ – 4x² + 4xanswer 3B) 6x³ – 4x² + 4x Explanation: The additive inverse is defined as what we add to a number/expression to get a result of “zero” Examples: -5 is the additive inverse of 5 because -5 + 5 = 0 - x² is the additive inverse of x² as x² – x² = 0 So to get the additive inverse just multiply the number/expression you have by -1 The given expression is: -6x³ + 4x² – 4x We get the inverse additive as follows: -1 (-6x³ + 4x² – 4x) -(-6x³) – (4x²) – (-4x) 6x³ – 4x² + 4x Hope this helpedanswer 4B. Walkthrough: Since the additive inverse of an expression or number is an expression or number which after addition yields the additive identity Read more